Mapping Student Data Using Data Warehouse for Promotion at Vocational High School of Z - Khoirudin Eko Nurcahyo; Sucipto Sucipto; Arie Nugroho (UNIVERSITAS PGRI MADIUN, 2020)
The purpose of this study is provide data warehouse modeling which make executive of school can analyze data easily, the problem is executive of school are analysis list registrant list difficulty, what the most and least registrant junior high school come from and the major which most and least registrant. This study do is because how important data management on education organization and how the data can be managed better. The study use descriptive quantitative method research and use 4 step data warehouse dimensional modeling by Kimball. On building data warehouse used ETL, data be extracted and transformed into data warehouse as dimension and fact. For next data be imported and be showed by web base business intelligence app. The result of this study is an web base business intelligence app which can show sum of registrant on gender, majors, junior high school graduate come from, recommendation and register year. Data warehouse is good at data analyzing for decision making, because data warehouse can show information quickly and accurate.